Obesity as A Predictor of Preeclampsia in High-Risk Pregnancies: A Literature Review - Chamy Rahmatiqa; Delmi Sulastri (Universitas Pahlawan Tuanku Tambusai, 2025)
Obesity in pregnant women is a major risk factor contributing to the increased incidence of preeclampsia, a serious pregnancy complication that significantly contributes to maternal morbidity and mortality. This study aims to examine the relationship between obesity and the incidence of preeclampsia in pregnant women, particularly in the context of high-risk pregnancies. It is a systematic review conducted in accordance with PRISMA guidelines. Articles were retrieved from the PubMed, ScienceDirect, Scopus, and Google Scholar databases. Eight articles meeting the inclusion criteria were analyzed narratively. The findings indicate that obesity significantly contributes to the incidence of preeclampsia, with a reported prevalence of up to 37.5%. Other predominant risk factors include maternal age extremes (<20 years or >35 years), hypertension, high parity, sociocultural conditions, and multiple pregnancies. The reviewed studies show that pre-pregnancy obesity increases the risk of preeclampsia proportionally to the class of obesity, with the highest risk observed at a BMI ≥40. In conclusion, obesity is a modifiable risk factor that plays a significant role in the occurrence of preeclampsia in high-risk pregnancies. These findings underscore the importance of early interventions and preventive efforts focused on maternal weight management. Keywords: preeclampsia, obesity, high-risk pregnancy, maternal mortality